A study of surgical outcome of necrotizing pancreatitis - Tukaram, Bhondave Suraj; Dash, Niranjan; Thipse, V. J.; Gadekar, J. M. (International Surgery Journal, 2017)
Background: Increasing understanding and literature regarding the management of Necrotizing Pancreatitis has laid paths for surgical and conservative management. Although a conservative approach is increasingly used, this study depicts the importance of surgical management in today’s era. The objective was to evaluate the surgical role in patients of documented Necrotizing Pancreatitis, with or without organ failure and debilitating symptoms by putting conservative management on a complementary part. Methods: Sixteen consecutive patients were reviewed with Necrotizing Pancreatitis managed at DVVPF’s Medical college and hospital, Ahmednagar between January 1, 2014, and July 1, 2017 documented by contrast-enhanced computed tomography (CECT). Results: Out of sixteen patients of Necrotizing Pancreatitis recruited for the study, 13 (81%) patients were surgically managed; among which death rate was 7%. Of the other 3(19%) patients which were conservatively managed, there was 1 (33%) death. Patient who died while conservative management would have been candidate for earlier surgical intervention. Conclusions: The results suggest that surgical approach can be applied successfully to manage most patients with Necrotizing Pancreatitis, still further evaluation being required for indication and timing of surgery.